Flow in open channels - Subramanya, K. (McGraw Hill Education, 2019)
This edition has been revised to cater to undergraduate and postgraduate students of Civil Engineering and those studying Open Channel Hydraulics. Besides it will also be useful to aspiring and practicing engineers. The book fulfills the syllabi requirement of majority of Indian universities. Offering learning objective-based enriched content, well-structured layout, and a strong pedagogy, it includes questions from competitive examinations as well.